Legal Analysis of Criminal Responsibility for Hackers From The Perspective of Cyber Law In Indonesia - Rusmana, I Putu Edi; Novelin, Tania (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Cybercrime, especially hacking, is a major challenge in the digital era, especially when perpetrators operate across countries. This study analyzes the effectiveness of Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) in combating international hacking crimes and evaluating international cooperation in cyber law enforcement. Using a normative legal approach, this study shows that although the ITE Law provides a strong legal basis, its application to perpetrators abroad faces jurisdictional challenges, differences in legal systems, and limitations in international cooperation. Technical obstacles in identifying and prosecuting perpetrators are also significant. To overcome this problem, it is necessary to strengthen international cooperation through extradition agreements and mutual legal assistance (MLA), as well as participation in international conventions such as the Budapest Convention. Increasing the technical capacity of law enforcement officers is also important to strengthen law enforcement against transnational hacking crimes. This study concludes that legal arrangements in Indonesia need to be improved through regulatory reform and more effective international cooperation so that Indonesia can protect national interests in the increasingly complex digital era.